ACADEMIC SELF-EFFICACY, STRESS AND COPING STRATEGIES AS PREDICTORS OF ACADEMIC PERFORMANCE AMONG STUDENTS IN PUBLIC PRIMARY TEACHER TRAINING COLLEGES IN CENTRAL REGION, KENYA - MUEMA, ELIZABETH NDINDA (Machakos University Press, 2022)
Poor performance has been reported in Kenya's Public Primary Teacher Training Colleges from 2014 onwards. The goal of this study was to see if there was a link between students' Academic Self-efficacy, Stress and coping strategies and academic performance in Kenya's Public Teacher Training Colleges in Central Region. The study's objectives were; To investigate the relationship between academic self-efficacy and academic performance among students in Primary Teacher Training Colleges in central Region. To establish the relationship between stress and academic performance among students in Public Primary Teacher Training Colleges in Central Region, Kenya. To establish the relationship between coping strategies and Academic Performance among students in Primary Teacher Training Colleges in Central region Kenya.; and lastly to establish gender differences in academic self-efficacy, stress, and coping strategies among students in Public Primary Teacher Training Colleges in Central Region. The Transactional and Self-efficacy theories were used to guide the research. The researcher employed a mixed research design. The study focused on all of Public Primary Kenya's Teacher Training colleges in Central Region. The curriculum deans, Lecturers and second-year students were the respondents. The sample size was 224 respondents, with 200 second-year students, four curriculum deans, and 20 lecturers. The central region colleges, deans, and students were all sampled using the purposive sampling method. Stratified sampling was used to get data on gender. Questionnaires, interviews, and document analysis were used to gather information based on the research objectives. The students' average grade from the mid-course tests was used to estimate their academic performance. Descriptive and inferential analysis were used to analyse quantitative data. The link between the variables was determined using Pearson Product Moment Correlation, while regression analysis was performed to determine the independent variables' predictions on the dependent variable. Thematic analysis was used to examine qualitative data. Academic self-efficacy was found to be a significant predictor of academic performance F (1 195) =189.08, p <0.05. (content understanding, time management, examination preparation and academic self-drive). Academic performance was also predicted by stress. F (4,192) = 58.5, p <0.05,(academic stressors, environmental stressors, intrapersonal and social stressors) Coping strategies predicted academic performance F (3,195) =89.73, p <0.05. Task oriented coping strategy had a positive prediction on academic performance while emotion oriented and avoidance oriented had a negative prediction on Academic performance: Gender differences in emotion-oriented coping and avoidance-oriented coping were found in favour of female students (t = -3.95, p < 0.05) and (t = -3.45, p<0.05) respectively. The study recommended that colleges should create an enhancing environment to foster the development of academic self-efficacy and positive coping strategies. Thus, students' support systems that improve academic performance should be bolstered. There should be deliberate measures to improve positive coping strategies among female students to help them respond appropriately to stressful situations.